Primary School Strategies in Recognizing and Developing Children's Potential from An Early Age: A Qualitative Study in Integrated Islamic Schools - Muhammad Arifudin; Muh. Nur Rochim Maksum; Mahasri Shobahiya (Universitas Muhammadiyah Surakarta, 2025)
Introduction and development of children's potential at the elementary school level play a crucial role in shaping students' academic, social, emotional, and moral development. However, studies addressing the development of children's potential in primary education tend to focus more on measurable learning outcomes and formal assessments, while research on school strategies, particularly in the context of integrated Islamic elementary schools, remains relatively limited. This study aims to examine the strategies employed by integrated Islamic elementary schools in identifying and developing children's potential from an early age, as well as to identify the factors that support and hinder the implementation of these strategies. This research uses a qualitative approach with a descriptive case study design conducted at one of the integrated Islamic elementary schools in Indonesia. Data were collected through in-depth interviews with the school principal and class teachers, observation of learning activities, and analysis of school documentation. The data obtained were analyzed using thematic analysis to identify patterns and main themes related to the strategies for recognizing and developing children's potential. The findings of this study show that the school implements a holistic and sustainable approach to identifying children's potential through systematic observation, differentiated learning, and intensive communication with parents. The development of both academic and non academic potential is integrated into learning activities, extracurricular activities, and character-building practices that align with the values of integrated Islamic education. Teachers' commitment, school management support, and parental involvement are key supporting factors, while limited time and the diversity of students' characteristics present challenges in the implementation of these strategies. Theoretically, this research enriches the study of school strategies in developing children's potential in primary education. Practically, the findings of this study can serve as a reference for elementary schools, particularly integrated Islamic schools, in designing contextual and sustainable strategies for developing children's potential.